Polymers with antimicrobial properties
Patent Information
- Application Number
- CN202580016137.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-02-07
- Filing Date
- 2025-02-07
- Publication Date
- 2026-10-13
AI Technical Summary
虽然这些共混材料中的一些显示出对各种细菌菌株例如金黄色葡萄球菌、大肠杆菌和铜绿假单胞菌的良好抗菌活性,但是观察到抗微生物剂的显著浸出,很可能是由于短烷基链与聚合物基质的不良缠结
Smart Images

Figure FT_1 
Figure FT_2 
Figure SMS_9
Abstract
Description
Technical Field
[0001] This invention relates to a functionalized polyolefin, a method for preparing the same, and polyolefin blends comprising the same. The functionalized polyolefin can be used as an antimicrobial polymer additive. Background Technology
[0002] Antimicrobial resistance and its impact on global health and related economic costs are receiving increasing attention. The overuse of antibiotics as prescription drugs has affected their efficacy, and many commonly used small-molecule antibiotics are now ineffective against certain treatments. Furthermore, there is a growing need to develop antimicrobial coatings and coatings for applications such as food packaging, medical devices, and antifouling coatings (e.g., ship hull coatings). An alternative to using small-molecule antibiotics or antimicrobial disinfectants is to utilize polymers with antimicrobial properties, which will prevent the spread of bacteria in the first place. Antimicrobial polymers offer several advantages, such as long-term activity, non-volatility, chemical stability, and minimal residual toxicity. Polymers with antimicrobial activity have become an important area of research, and many different materials have entered the market, along with regulatory standards such as ISO 22196. One approach is to incorporate metal ions, such as copper or silver, but these materials often have a limited lifespan because the metal ions gradually leach out of the polymer material. Biocidal polymers (the type of polymer studied in this paper) are polymers that possess inherent antimicrobial activity due to the presence of functional groups. Examples of functional groups that have exhibited antimicrobial properties include quaternary ammonium ions (quaternary ammonium compounds) and related guanidinium cations, amidineium cations, imidazolium cations, and phosphonium cations. In addition to ionic interactions, hydrogen bonds are also considered crucial for effective antimicrobial activity; therefore, protonated primary and secondary amines interact more strongly with bacterial cell membranes than quaternary ammonium ions due to the presence of hydrogen bonds.
[0003] The widespread use of small-molecule antimicrobial agents, including quaternary ammonium compounds, and their post-use fate have raised several environmental issues, as their disposal can lead to ecological harm. Using polymeric quaternary ammonium compounds as polymer additives can address this problem by incorporating the active ingredient into the host polymer, thereby creating an antimicrobial polymer surface after melt blending. FF Rossetti, K. Siegmann, J. Köser, I. Wegner, I. Keskin, G. Schlotterbeck and M. Winkler, *International Journal of Polymer Science*, 2017, 1-10, describes antimicrobial polymers with C... 18The use of alkyl-chain quaternary ammonium compounds, which are melt-blended with LDPE. While some of these blends show good antimicrobial activity against various bacterial strains such as Staphylococcus aureus, Escherichia coli, and Pseudomonas aeruginosa, significant leaching of the antimicrobial agent has been observed, likely due to poor entanglement of the short alkyl chains with the polymer matrix. Similar observations have been made in US20160150778 and EP2824139.
[0004] There is a need for an effective antimicrobial polymer that does not exhibit leaching of antimicrobial agents and has good mechanical and thermal properties. Summary of the Invention
[0005] In a first aspect, this article provides a functionalized polyolefin of the formula PO-X, wherein PO is a polyolefin with a chain length of at least 20 carbon atoms, and X is a positively charged functional group or a functional group capable of forming a cation at pH 7.
[0006] In a second aspect, this article provides a method for preparing a functionalized polyolefin according to the first aspect, the method comprising reacting Zn(PO)2 with iodine to obtain PO-I, and reacting PO-I to obtain PO-X, wherein PO has a chain length of at least 20 carbon atoms.
[0007] In a third aspect, this document provides a polyolefin blend comprising a first polyolefin and a second polyolefin, wherein the first polyolefin is a functionalized polyolefin according to the first aspect.
[0008] In a fourth aspect, this article provides a method for preparing a polyolefin blend according to the third aspect, the method comprising melt blending a first polyolefin with a second polyolefin.
[0009] In a fifth aspect, this article provides the use of functionalized polyolefins according to the first aspect as antimicrobial polymer additives.
[0010] In a sixth aspect, this article provides a method for imparting antimicrobial properties to a surface, the method comprising applying a functionalized polyolefin according to a first aspect or a polyolefin blend according to a third aspect to the surface.
[0011] In a seventh aspect, this document provides a surface or article comprising (i) a functionalized polyolefin according to the first aspect or (ii) a polyolefin blend according to the second aspect. Attached Figure Description
[0012] Figure 1 The change in fold increase of viable bacteria compared to the LDPE control is shown. **Statistical significance is indicated by a p-value < 0.001.
[0013] Figure 2 The weight fraction of active antimicrobial compounds in the PE additives is shown. Detailed Implementation
[0014] Commercial availability of alkyl chains, typically derived from natural fatty acids in the form of alkyl halides, is limited to chains with a length not exceeding C. 18 Given the low entanglement molecular weight (T) of polyethylene e (≈1200 Da), longer alkyl chains should ensure that the antimicrobial agent is permanently entangled within the PE matrix during melt blending, thereby minimizing the risk of leaching of the active antimicrobial agent into the environment. The method described herein can synthesize various chain lengths, such as an average of C ≈1200 Da. 18 C 30 C 68 and C 180 As described in R. von Goetze, A. Aljaber, K.-Y. Lee, G. Hill, C. Wallis and GJP Britovsek, Polymer Chemistry, 2022, 13, 6377-6385 (incorporated hereby by reference), these longer-chain alkyl halides are readily prepared from diethylzinc and ethylene via a catalytic chain-growth reaction (CCG) to generate ZnPE2. After quenching with, for example, iodine, this unique CCG method based on an iron bis(imino)pyridine catalyst and diethylzinc produces 1-iodoalkanes of any desired chain length with high selectivity, exhibiting a Poisson distribution.
[0015] This document describes a functionalized polyolefin of the formula PO-X, wherein PO is a polyolefin with a chain length of at least 20 carbon atoms. X can be a positively charged functional group. X can be a functional group capable of forming a cation at pH 7. X can be a polar part of antimicrobial activity. The functionalized polyolefins described herein can be used as antimicrobial polymer additives and in methods for imparting antimicrobial properties to surfaces.
[0016] Antimicrobial active groups
[0017] X is an antimicrobial active group that can interact with negatively charged cell membranes and disrupt their structure. Due to its polarity, X repels nonpolar polymer matrices (such as second polyolefins in polymer blends as described herein) and diffuses to the surface, thereby providing antimicrobial activity on the polymer surface.
[0018] As described in this article, X is present at the end of the polyolefin chain. Therefore, "PO-X" means that X is present at the end of the polyolefin (PO) chain. PO-X can be described as a terminally functionalized polyolefin.
[0019] X can be a cation or be able to form a cation at pH 7, wherein the cation is selected from ammonium cations, phosphonium cations, pyridinium cations, imidazolium cations, amidonium cations, and guanidinium cations.
[0020] Ammonium cations can be represented by the following formula:
[0021] ,
[0022] Each R 1 Independently selected from H and organic moieties, such as alkyl groups (e.g., C1-C). 10 Alkyl (e.g., C3-C) 10 cycloalkyl), C1-C6 alkyl or C1-C2 alkyl), alkenyl (e.g., C2-C6 alkyl), alkenyl (e.g., C1-C6 alkyl or C1-C2 alkyl), alkenyl (e.g., C2-C6 alkyl) 10 alkenyl, C2-C6 alkenyl or C2-C3 alkenyl), alkynyl (e.g., C2-C... 10 alkynyl, C2-C6 alkynyl or C2-C3 alkynyl), aryl (e.g., C6-C...) 10 aryl) or heteroaryl (e.g., C5-C) 10 (Heteroaryl). It should be understood that each organic moiety may optionally be substituted with, for example, a halogen, amino, thiol, alkoxy (e.g., C1-C6 alkoxy or C1-C2 alkoxy), -OH group, or a combination thereof. In some embodiments, the ammonium cation is a quaternary ammonium cation, i.e., each R 1 None of them are H.
[0023] The phosphonium cation can be represented by the following formula:
[0024] ,
[0025] Each R 2 Independently selected from H and organic moieties, such as alkyl groups (e.g., C1-C). 10 Alkyl (e.g., C3-C) 10 cycloalkyl), C1-C6 alkyl or C1-C2 alkyl), alkenyl (e.g., C2-C6 alkyl), alkenyl (e.g., C1-C6 alkyl or C1-C2 alkyl), alkenyl (e.g., C2-C6 alkyl) 10 alkenyl, C2-C6 alkenyl or C2-C3 alkenyl), alkynyl (e.g., C2-C... 10 alkynyl, C2-C6 alkynyl or C2-C3 alkynyl), aryl (e.g., C6-C...) 10 aryl) or heteroaryl (e.g., C5-C) 10 (Heteroaryl). It should be understood that each organic moiety may optionally be substituted with, for example, a halogen, amino, thiol, alkoxy (e.g., C1-C6 alkoxy or C1-C2 alkoxy), -OH group, or a combination thereof. In some embodiments, the cation is a quaternary cation, i.e., each R 2 None of them are H.
[0026] The pyridinium cation can be represented by the following formula:
[0027] ,
[0028] Each R 3 (If present) can be independently selected from halogens, amino groups, thiol groups, -OH groups, alkyl groups (e.g., C1-C). 10 Alkyl (e.g., C3-C) 10 cycloalkyl), C1-C6 alkyl or C1-C2 alkyl), alkenyl (e.g., C2-C6 alkyl), alkenyl (e.g., C1-C6 alkyl or C1-C2 alkyl), alkenyl (e.g., C2-C6 alkyl) 10 alkenyl, C2-C6 alkenyl or C2-C3 alkenyl), alkynyl (e.g., C2-C... 10 alkynyl, C2-C6 alkynyl or C2-C3 alkynyl), aryl (e.g., C6-C...) 10 aryl), heteroaryl (e.g., C5-C) 10 The organic moiety may be a heteroaryl, alkenyl, alkynyl, aryl, heteroaryl, or alkoxy group, or a combination thereof. It should be understood that each organic moiety (e.g., alkyl, alkenyl, alkynyl, aryl, heteroaryl, and alkoxy) may optionally be substituted with, for example, a halogen, amino, thiol, alkoxy (e.g., C1-C6 or C1-C2 alkoxy), -OH group, or a combination thereof. In some embodiments, the pyridinium cation is pyridinium (i.e., R is absent). 3 ).
[0029] The imidazolium cation can be represented by the following formula:
[0030] ,
[0031] Where R 4 It can be selected from H and organic moieties, such as alkyl (e.g., C1-C). 10 Alkyl (e.g., C3-C) 10 cycloalkyl (or C1-C6 alkyl), alkenyl (e.g., C2-C6) 10 alkenyl), alkynyl (e.g., C2-C) 10 alkynyl), aryl (e.g., C6-C) 10 aryl) or heteroaryl (e.g., C5-C) 10 (heteroaryl), and R 5 It can be selected from H, halogen, amino, thiol group, -OH group, alkyl (e.g., C1-C) 10 Alkyl (e.g., C3-C) 10 cycloalkyl), C1-C6 alkyl or C1-C2 alkyl), alkenyl (e.g., C2-C6 alkyl), alkenyl (e.g., C1-C6 alkyl or C1-C2 alkyl), alkenyl (e.g., C2-C6 alkyl) 10 alkenyl, C2-C6 alkenyl or C2-C3 alkenyl), alkynyl (e.g., C2-C... 10 alkynyl, C2-C6 alkynyl or C2-C3 alkynyl), aryl (e.g., C6-C...)10 aryl), heteroaryl (e.g., C5-C) 10 The organic moiety can be a heteroaryl group, an alkoxy group (e.g., C1-C6 alkoxy or C1-C2 alkoxy), or a combination thereof. It should be understood that each organic moiety may optionally be substituted with, for example, a halogen, an amino group, a thiol group, an alkoxy group (e.g., C1-C6 alkoxy or C1-C2 alkoxy), an -OH group, or a combination thereof. In some embodiments, the imidazolium cation is imidazolium (i.e., R...). 4 and R 5 All are H).
[0032] The amidonium cation can be represented by the following formula:
[0033] ,
[0034] Each R 6 Independently selected from H and organic moieties, such as alkyl groups (e.g., C1-C). 10 Alkyl (e.g., C3-C) 10 cycloalkyl), C1-C6 alkyl or C1-C2 alkyl), alkenyl (e.g., C2-C6 alkyl), alkenyl (e.g., C1-C6 alkyl or C1-C2 alkyl), alkenyl (e.g., C2-C6 alkyl) 10 alkenyl, C2-C6 alkenyl or C2-C3 alkenyl), alkynyl (e.g., C2-C... 10 alkynyl, C2-C6 alkynyl or C2-C3 alkynyl), aryl (e.g., C6-C...) 10 aryl) or heteroaryl (e.g., C5-C) 10 (Heteroaryl). It should be understood that each organic moiety may optionally be substituted with, for example, a halogen, amino, thiol, alkoxy (e.g., C1-C6 alkoxy or C1-C2 alkoxy), -OH group or a combination thereof.
[0035] The guanidinium cation can be represented by the following formula:
[0036] ,
[0037] Each R 7 Independently selected from H and organic moieties, such as alkyl groups (e.g., C1-C). 10 Alkyl (e.g., C3-C) 10 cycloalkyl), C1-C6 alkyl or C1-C2 alkyl), alkenyl (e.g., C2-C6 alkyl), alkenyl (e.g., C1-C6 alkyl or C1-C2 alkyl), alkenyl (e.g., C2-C6 alkyl) 10 alkenyl, C2-C6 alkenyl or C2-C3 alkenyl), alkynyl (e.g., C2-C... 10 alkynyl, C2-C6 alkynyl or C2-C3 alkynyl), aryl (e.g., C6-C...) 10 aryl) or heteroaryl (e.g., C5-C) 10(Heteroaryl). It should be understood that each organic moiety may optionally be substituted with, for example, a halogen, amino, thiol, alkoxy (e.g., C1-C6 alkoxy or C1-C2 alkoxy), -OH group or a combination thereof.
[0038] Chain length
[0039] As used herein, "chain" refers to the backbone (backbone) of a polymer (e.g., polyolefin). Therefore, "chain length" refers to the number of atoms (e.g., carbon atoms) in the chain. For example, in the following example, where PO is PE and n is 31, the chain length is 66 carbon atoms: Similarly, for PP with the following structure, where n is 18 and the chain length is 39 carbon atoms: .
[0040] To ensure permanent entanglement of the functionalized polyolefin (PO-X) within another polyolefin (e.g., a second polyolefin in a polymer blend as described herein), the chain length of PO-X should preferably be greater than the entanglement molecular weight of the other polyolefin. For linear polyethylene (PE), the entanglement molecular weight is approximately 1000 g / mol to 1200 g / mol (C 70 -C 80 However, for branched PE, the entangled molecular weight is shorter. As described herein, PO has a chain length of at least 20 carbon atoms. As the chain length increases, the functionalization of a given chain becomes more difficult because the chain length affects solubility. In some embodiments, the PO chain of PO-X contains 20 to 100 carbon atoms, 24 to 96 carbon atoms, 26 to 92 carbon atoms, 30 to 90 carbon atoms, 34 to 88 carbon atoms, 38 to 86 carbon atoms, 42 to 84 carbon atoms, 46 to 82 carbon atoms, 50 to 80 carbon atoms, 54 to 76 carbon atoms, or 60 to 70 carbon atoms. In some embodiments, the PO chain of PO-X contains an average of 20 to 100 carbon atoms, 24 to 96 carbon atoms, 26 to 92 carbon atoms, 30 to 90 carbon atoms, 34 to 88 carbon atoms, 38 to 86 carbon atoms, 42 to 84 carbon atoms, 46 to 82 carbon atoms, 50 to 80 carbon atoms, 54 to 76 carbon atoms, or 60 to 70 carbon atoms. In some embodiments, the PO chain of PO-X contains an average of 50 to 80 carbon atoms.
[0041] The average number of carbon atoms in the chain can be determined using methods known to those skilled in the art, such as... 13 C-NMR or GC analysis. The method described in this paper produces a Poisson distribution for linear alkanes. This allows for quantitative analysis. 13 C10 NMR analysis is used to estimate the average chain length by comparing the integrals of the CH3 and CH2 signals. nFurther analysis can be performed using GC-FID. The average molecular weight is generally too low for accurate GPC analysis, and GC-FID analysis only yields a portion of the total distribution because longer alkanes are only partially soluble and insufficiently volatile for GC analysis. Therefore, only the first part of the total distribution is quantifiable, and these values can be used as input to the Poisson equation to extract λ, the average number of inserted ethylene units (L is the amount of catalyst used). The total amount of each alkane with chain length n obtained at the end of the reaction can then be calculated.
[0042]
[0043] The comparison of the average chain lengths determined by GC and NMR analyses showed excellent agreement.
[0044] Therefore, when this article refers to "average" chain length, it means through 13 Average chain length determined by C10 NMR analysis C n Alternatively, this can refer to the average chain length as determined by GC (e.g., GC-FID).
[0045] Besides referencing M n Apart from the value, there seems to be no convenient nomenclature to describe mixtures of compounds with long alkyl chains, where the chain lengths follow a Poisson distribution. To describe the chain lengths in the product mixture, the italicized value of n (n) is used in this paper to describe the average chain length, i.e., C0. n H 2n±2 This nomenclature is used to describe mixtures of alkanes with an average chain length of n. The same nomenclature is used for other related compounds, namely Zn(C 30 H 61 )2 After hydrolysis, C will be produced 30 H 62 It may react with iodine to produce C 30 H 61 I.
[0046] polymer blends
[0047] This document describes a polyolefin blend comprising a first polyolefin and a second polyolefin, wherein the first polyolefin is a functionalized polyolefin as described herein. It should be understood that the second polyolefin is structurally different from the first polyolefin.
[0048] The first polyolefin and the second polyolefin may each contain the same repeating unit. For example, the first polyolefin may be functionalized polyethylene and the second polyolefin may be polyethylene. Alternatively, the first polyolefin and the second polyolefin may each contain different repeating units. For example, the first polyolefin may be functionalized polyethylene and the second polyolefin may be polypropylene.
[0049] When referring to component loading, this is relative to the total mass. For example, for a polymer blend in which PE-X (where X is an antimicrobial agent) is present at a loading of 2 wt%, 10 g of the polymer blend contains 0.2 g of PE-X.
[0050] When incorporated into polymer blends, even very low loadings of functionalized polyolefins can provide antimicrobial properties. In polymer blends as described herein, the first (functionalized) polyolefin may be provided in loadings of at least 0.01 wt%, at least 0.05 wt%, at least 0.1 wt%, at least 0.5 wt%, at least 0.75 wt%, at least 1 wt%, at least 1.25 wt%, at least 1.5 wt%, at least 1.75 wt%, or at least 2 wt% relative to the total mass of the polyolefin blend. The first (functionalized) polyolefin may be provided in loadings of at most 4 wt%, at most 3.5 wt%, at most 3 wt%, at most 2.5 wt%, at most 2 wt%, at most 1.75 wt%, at most 1.5 wt%, at most 1.25 wt%, at most 1 wt%, at most 0.75 wt%, or at most 0.5 wt% relative to the total mass of the polyolefin blend. For example, the first (functionalized) polyolefin may be provided in loadings of 0.01 wt% to 4 wt%, 0.05 wt% to 3 wt%, 0.1 wt% to 2.5 wt%, 0.5 wt% to 2 wt% or 1 wt% to 2 wt% relative to the total mass of the polyolefin blend. In some embodiments, the first (functionalized) polyolefin may be provided in loadings of about 2 wt% relative to the total mass of the polyolefin blend.
[0051] Methods for preparing functionalized polyolefins and polyolefin blends
[0052] The functionalized polyolefins described herein can be prepared, for example, by a method comprising reacting Zn(PO)₂ with iodine to obtain PO-I and reacting PO-I to obtain PO-X, wherein PO has a chain length of at least 20 carbon atoms. Zn(PO)₂ can be produced by polymerizing olefins in the presence of an alkyl zinc and a catalyst system. The step of reacting PO-I to obtain PO-X will depend on the characteristics of X. For example, this step may include reacting PO-I with a tertiary amine, with pyridine, or with a tertiary phosphine. In some embodiments, PO-I can be converted to PO-NH₂ and subsequently reacted with cyanoguanidine.
[0053] As described herein, functionalized polyolefins can be incorporated into polyolefin blends. The polyolefin blends described herein can be prepared, for example, by melt blending a functionalized polyolefin with a second polyolefin.
[0054] As described herein, aspects and embodiments of functionalized polyolefins, methods for preparing functionalized polyolefins, polyolefin blends, methods for preparing polyolefin blends, uses of functionalized polyolefins, methods for imparting antimicrobial properties to surfaces, and surfaces or articles comprising functionalized polyolefins or polyolefin blends are set forth in the following clauses.
[0055] 1. A functionalized polyolefin of formula PO-X, wherein:
[0056] PO is a polyolefin with a chain length of at least 20 carbon atoms; and
[0057] X is a positively charged functional group or a functional group that can form a cation at pH 7.
[0058] 2. Functionalized polyolefins according to Clause 1, wherein PO is polyethylene (PE) or polypropylene (PP).
[0059] 3. Functionalized polyolefins according to Clause 2, wherein PO is polyethylene (PE).
[0060] 4. A functionalized polyolefin according to any of the foregoing clauses, wherein X is a positively charged functional group.
[0061] 5. A functionalized polyolefin according to any of the preceding clauses, wherein X is selected from ammonium cation, phosphonium cation, pyridinium cation, imidazolium cation, amidonium cation and guanidinium cation.
[0062] 6. A functionalized polyolefin according to any of the preceding clauses, wherein X is selected from ammonium cations, phosphonium cations, pyridinium cations, and guanidinium cations.
[0063] 7. A functionalized polyolefin according to any of the foregoing clauses, wherein X is selected from ammonium cations, pyridinium cations, and guanidinium cations.
[0064] 8. A functionalized polyolefin according to any of the foregoing clauses, wherein X is an ammonium cation.
[0065] 9. Functionalized polyolefins according to Clause 8, wherein the ammonium cation is a quaternary ammonium cation.
[0066] 10. A functionalized polyolefin according to any of the foregoing clauses, wherein X is a pyridinium cation.
[0067] 11. A functionalized polyolefin according to any of the foregoing clauses, wherein X is a guanidinium cation.
[0068] 12. A functionalized polyolefin according to any of the foregoing clauses, wherein X is a phosphonium cationic cation.
[0069] 13. Functionalized polyolefins according to Clause 12, wherein the phosphonium cation is a quaternary phosphonium cation.
[0070] 14. A functionalized polyolefin according to any of the preceding clauses, wherein X is a functional group capable of forming a cationic group at pH 7.
[0071] 15. A functionalized polyolefin according to any of the preceding clauses, wherein the cation is selected from ammonium cations, phosphonium cations, pyridinium cations, imidazolium cations, amidonium cations, and guanidinium cations.
[0072] 16. A functionalized polyolefin according to any of the preceding clauses, wherein the cation is selected from ammonium cations, phosphonium cations, pyridinium cations and guanidineium cations.
[0073] 17. A functionalized polyolefin according to any of the preceding clauses, wherein the cation is selected from ammonium cations, pyridinium cations, and guanidinium cations.
[0074] 18. A functionalized polyolefin according to any of the foregoing clauses, wherein the cation is an ammonium cation.
[0075] 19. Functionalized polyolefins pursuant to Clause 18, wherein the ammonium cation is a quaternary ammonium cation.
[0076] 20. A functionalized polyolefin according to any of the foregoing clauses, wherein the cation is a pyridinium cation.
[0077] 21. A functionalized polyolefin according to any of the foregoing clauses, wherein the cation is a guanidinium cation.
[0078] 22. A functionalized polyolefin according to any of the foregoing clauses, wherein X is selected from:
[0079] , and .
[0080] 23. A functionalized polyolefin according to any of the foregoing clauses, wherein the cation is a phosphonium cation.
[0081] 24. Functionalized polyolefins according to Clause 23, wherein the phosphonium cation is a quaternary phosphonium cation.
[0082] 25. A functionalized polyolefin according to any of the preceding clauses, wherein X is selected from triphenylphosphonium and tributylphosphonium.
[0083] 26. A functionalized polyolefin according to any of the foregoing clauses, wherein the chain length of PO follows a Poisson distribution.
[0084] 27. A functionalized polyolefin according to any of the preceding clauses, wherein the PO has a chain length of 20 to 200 carbon atoms.
[0085] 28. A functionalized polyolefin according to any of the preceding clauses, wherein the PO has a chain length of 20 to 180 carbon atoms.
[0086] 29. A functionalized polyolefin according to any of the preceding clauses, wherein the PO has a chain length of 20 to 100 carbon atoms.
[0087] 30. A functionalized polyolefin according to any of the preceding clauses, wherein the PO has a chain length of 24 to 96 carbon atoms.
[0088] 31. A functionalized polyolefin according to any of the preceding clauses, wherein the PO has a chain length of 26 to 92 carbon atoms.
[0089] 32. A functionalized polyolefin according to any of the preceding clauses, wherein the PO has a chain length of 30 to 90 carbon atoms.
[0090] 33. A functionalized polyolefin according to any of the preceding clauses, wherein the PO has a chain length of 34 to 88 carbon atoms.
[0091] 34. A functionalized polyolefin according to any of the preceding clauses, wherein the PO has a chain length of 38 to 86 carbon atoms.
[0092] 35. A functionalized polyolefin according to any of the preceding clauses, wherein the PO has a chain length of 42 to 84 carbon atoms.
[0093] 36. A functionalized polyolefin according to any of the preceding clauses, wherein the PO has a chain length of 46 to 82 carbon atoms.
[0094] 37. A functionalized polyolefin according to any of the preceding clauses, wherein the PO has a chain length of 50 to 80 carbon atoms.
[0095] 38. A functionalized polyolefin according to any of the preceding clauses, wherein the PO has a chain length of 54 to 76 carbon atoms.
[0096] 39. A functionalized polyolefin according to any of the preceding clauses, wherein the PO has a chain length of 60 to 70 carbon atoms.
[0097] 40. A functionalized polyolefin according to any of the preceding clauses, wherein the PO has an average chain length of 20 to 200 carbon atoms.
[0098] 41. A functionalized polyolefin according to any of the preceding clauses, wherein the PO has an average chain length of 20 to 180 carbon atoms.
[0099] 42. A functionalized polyolefin according to any of the preceding clauses, wherein the PO has an average chain length of 20 to 100 carbon atoms.
[0100] 43. A functionalized polyolefin according to any of the preceding clauses, wherein the PO has an average chain length of 24 to 96 carbon atoms.
[0101] 44. A functionalized polyolefin according to any of the preceding clauses, wherein the PO has an average chain length of 26 to 92 carbon atoms.
[0102] 45. A functionalized polyolefin according to any of the preceding clauses, wherein the PO has an average chain length of 30 to 90 carbon atoms.
[0103] 46. A functionalized polyolefin according to any of the preceding clauses, wherein the PO has an average chain length of 34 to 88 carbon atoms.
[0104] 47. A functionalized polyolefin according to any of the preceding clauses, wherein the PO has an average chain length of 38 to 86 carbon atoms.
[0105] 48. A functionalized polyolefin according to any of the preceding clauses, wherein the PO has an average chain length of 42 to 84 carbon atoms.
[0106] 49. A functionalized polyolefin according to any of the preceding clauses, wherein the PO has an average chain length of 46 to 82 carbon atoms.
[0107] 50. A functionalized polyolefin according to any of the preceding clauses, wherein the PO has an average chain length of 50 to 80 carbon atoms.
[0108] 51. A functionalized polyolefin according to any of the preceding clauses, wherein the PO has an average chain length of 54 to 76 carbon atoms.
[0109] 52. A functionalized polyolefin according to any of the preceding clauses, wherein the PO has an average chain length of 60 to 70 carbon atoms.
[0110] 53. A functionalized polyolefin according to any of the preceding clauses or any of clauses 55 to 57, wherein the functionalized polyolefin exhibits antimicrobial activity against Gram-negative bacteria.
[0111] 54. Functionalized polyolefins according to Clause 53, wherein the Gram-negative bacterium is Escherichia coli.
[0112] 55. A functionalized polyolefin of the formula PO-X, wherein:
[0113] PO is a polyolefin with a chain length of at least 20 carbon atoms; and
[0114] X is the polar part of the antimicrobial activity.
[0115] 56. A functionalized polyolefin of the formula PO-X, wherein:
[0116] PO is a polyolefin with an average chain length of at least 20 carbon atoms; and
[0117] X is a positively charged functional group or a functional group that can form a cation at pH 7.
[0118] 57. A functionalized polyolefin of the formula PO-X, wherein:
[0119] PO is a polyolefin with an average chain length of at least 20 carbon atoms; and
[0120] X is the polar part of the antimicrobial activity.
[0121] 58. Functionalized polyolefins according to any one of Clauses 55 to 57, wherein PO and / or X are as defined in any one of Clauses 2 to 52.
[0122] 59. A method for preparing a functionalized polyolefin according to any one of claims 1 to 58, the method comprising:
[0123] Reaction of Zn(PO)₂ with iodine to obtain PO₄⁻I; and
[0124] To obtain PO-X by reacting PO-I,
[0125] PO has a chain length of at least 20 carbon atoms.
[0126] 60. The method according to Clause 59, wherein Zn(PO)2 is produced by polymerizing olefins in the presence of alkyl zinc and a catalyst system.
[0127] 61. The method according to Clause 60, wherein the alkyl zinc is ZnEt2.
[0128] 62. The method according to clause 59 or 60, wherein the olefin is selected from ethylene and propylene.
[0129] 63. The method according to clause 62, wherein the olefin is ethylene.
[0130] 64. The method according to clause 62, wherein the olefin is propylene.
[0131] 65. The method according to any one of clauses 60 to 64, wherein the catalyst system comprises a group 3 to 10 transition metal, a group 3 main metal, a lanthanide, or an actinide.
[0132] 66. The method according to any one of clauses 60 to 65, wherein the catalyst system comprises iron.
[0133] 67. The method according to any one of clauses 60 to 66, wherein the catalyst system comprises bis(imino)pyridine.
[0134] 68. The method according to any one of clauses 60 to 67, wherein the catalyst system comprises [(2,6-diacetylpyridine bis(2,6-diisopropylaniline))FeCl2].
[0135] 69. The method according to any one of clauses 60 to 68, wherein the catalyst system further comprises methylaluminoxane (MAO).
[0136] 70. The method according to any one of clauses 61 to 69, wherein the ratio of Zn present in ZnEt2 to Fe present in the catalyst system is 270 to 500 molar equivalents.
[0137] 71. The method according to Clause 70, wherein the ratio of Zn present in ZnEt2 to Fe present in the catalyst system is 300 to 450 molar equivalents.
[0138] 72. The method according to any one of clauses 59 to 71, wherein reacting PO-I to obtain PO-X comprises reacting PO-I with a tertiary amine.
[0139] 73. The method according to Clause 72, wherein the tertiary amine is dimethylbenzylamine.
[0140] 74. The method according to clause 72 or 73, wherein the reaction with the tertiary amine is carried out in butanone.
[0141] 75. The method according to clause 72 or 73, wherein the reaction with the tertiary amine is carried out by reflux in the tertiary amine, optionally wherein the PO has a chain length of 50 to 80 carbon atoms or an average of 50 to 80 carbon atoms.
[0142] 76. The method according to any one of clauses 59 to 71, wherein reacting PO-I to obtain PO-X comprises reacting PO-I with pyridine.
[0143] 77. The method according to Clause 76, wherein pyridine is pyridine.
[0144] 78. The method according to clause 76 or 77, wherein the reaction with pyridine is carried out in toluene, butanone, 1,2,4-trichlorobenzene or N,N-dimethylformamide.
[0145] 79. The method according to clause 76 or 77, wherein the reaction with pyridine is carried out by reflux in pyridine, optionally wherein PO has a chain length of 50 to 80 carbon atoms or an average of 50 to 80 carbon atoms.
[0146] 80. The method according to any one of clauses 59 to 71, wherein reacting PO-I to obtain PO-X comprises:
[0147] PO-I is reacted with azides to obtain PO-N3;
[0148] Reduce azides to obtain PO-NH2; and
[0149] To react PO-NH2 with cyanoguanidine.
[0150] 81. The method according to Clause 80, wherein the reduction of azides is carried out using LiAlH4.
[0151] 82. The method according to Clause 80, wherein the reduction of azides is carried out using H2 and Pd / C.
[0152] 83. The method according to any one of clauses 59 to 71, wherein reacting PO-I to obtain PO-X comprises:
[0153] Reacting PO-I with NH3 to obtain PO-NH2; and
[0154] To react PO-NH2 with cyanoguanidine.
[0155] 84. The method according to Clause 83, wherein NH3 is provided in excess.
[0156] 85. The method according to clause 83 or 84, wherein the reaction between PO-I and NH3 is carried out in toluene.
[0157] 86. The method according to any one of clauses 83 to 85, wherein the reaction between PO-NH2 and cyanoguanidine is carried out in n-butanol.
[0158] 87. The method according to any one of clauses 83 to 86, wherein cyanoguanidine is p-chlorophenylcyanoguanidine.
[0159] 88. The method according to any one of clauses 59 to 71, wherein reacting PO-I to obtain PO-X comprises reacting PO-I with tertiary phosphine.
[0160] 89. The method according to Clause 88, wherein the tertiary phosphine is PPh3.
[0161] 90. The method according to Clause 88, wherein the tertiary phosphine is PBu3.
[0162] 91. The method according to any one of clauses 88 to 90, wherein the reaction with tertiary phosphine is carried out in toluene.
[0163] 92. A functionalized polyolefin that can be obtained by any one of the methods in clauses 59 to 91.
[0164] 93. A polyolefin blend comprising a first polyolefin and a second polyolefin, wherein the first polyolefin is a functionalized polyolefin as defined in any one of clauses 1 to 58 or 92.
[0165] 94. A polyolefin blend pursuant to Clause 93, wherein the first polyolefin is provided in a loading of at least 0.01 wt% relative to the total mass of the polyolefin blend.
[0166] 95. A polyolefin blend according to clause 93 or 94, wherein the first polyolefin is provided in a loading of at least 0.05 wt% relative to the total mass of the polyolefin blend.
[0167] 96. A polyolefin blend according to any one of clauses 93 to 95, wherein the first polyolefin is provided in a loading of at least 0.1 wt% relative to the total mass of the polyolefin blend.
[0168] 97. A polyolefin blend according to any one of clauses 93 to 96, wherein the first polyolefin is provided in a loading of at least 0.5 wt% relative to the total mass of the polyolefin blend.
[0169] 98. A polyolefin blend according to any one of clauses 93 to 97, wherein the first polyolefin is provided in a loading of at least 0.75 wt% relative to the total mass of the polyolefin blend.
[0170] 99. A polyolefin blend according to any one of clauses 93 to 98, wherein the first polyolefin is provided in a loading of at least 1 wt% relative to the total mass of the polyolefin blend.
[0171] 100. A polyolefin blend according to any one of clauses 93 to 99, wherein the first polyolefin is provided in a loading of at least 1.25 wt% relative to the total mass of the polyolefin blend.
[0172] 101. A polyolefin blend according to any one of clauses 93 to 100, wherein the first polyolefin is provided in a loading of at least 1.5 wt% relative to the total mass of the polyolefin blend.
[0173] 102. A polyolefin blend according to any one of clauses 93 to 101, wherein the first polyolefin is provided in a loading of at least 1.75 wt% relative to the total mass of the polyolefin blend.
[0174] 103. A polyolefin blend according to any one of clauses 93 to 102, wherein the first polyolefin is provided in a loading of at least 2 wt% relative to the total mass of the polyolefin blend.
[0175] 104. A polyolefin blend according to any one of clauses 93 to 103, wherein the first polyolefin is provided in a loading of up to 4 wt% relative to the total mass of the polyolefin blend.
[0176] 105. A polyolefin blend according to any one of clauses 93 to 104, wherein the first polyolefin is provided in a loading of up to 3.5 wt% relative to the total mass of the polyolefin blend.
[0177] 106. A polyolefin blend according to any one of clauses 93 to 105, wherein the first polyolefin is provided in a loading of up to 3 wt% relative to the total mass of the polyolefin blend.
[0178] 107. A polyolefin blend according to any one of clauses 93 to 106, wherein the first polyolefin is provided in a loading of up to 2.5 wt% relative to the total mass of the polyolefin blend.
[0179] 108. A polyolefin blend according to any one of clauses 93 to 107, wherein the first polyolefin is provided in a loading of up to 2 wt% relative to the total mass of the polyolefin blend.
[0180] 109. A polyolefin blend according to any one of clauses 93 to 108, wherein the first polyolefin is provided in a loading of up to 1.75 wt% relative to the total mass of the polyolefin blend.
[0181] 110. A polyolefin blend according to any one of clauses 93 to 109, wherein the first polyolefin is provided in a loading of up to 1.5 wt% relative to the total mass of the polyolefin blend.
[0182] 111. A polyolefin blend according to any one of clauses 93 to 110, wherein the first polyolefin is provided in a loading of up to 1.25 wt% relative to the total mass of the polyolefin blend.
[0183] 112. A polyolefin blend according to any one of clauses 93 to 111, wherein the first polyolefin is provided in a loading of up to 1 wt% relative to the total mass of the polyolefin blend.
[0184] 113. A polyolefin blend according to any one of clauses 93 to 112, wherein the first polyolefin is provided in a loading of up to 0.75 wt% relative to the total mass of the polyolefin blend.
[0185] 114. A polyolefin blend according to any one of clauses 93 to 113, wherein the first polyolefin is provided in a loading of up to 0.5 wt% relative to the total mass of the polyolefin blend.
[0186] 115. A polyolefin blend according to any one of clauses 93 to 114, wherein the first polyolefin is provided in a loading of 0.01 wt% to 4 wt% relative to the total mass of the polyolefin blend.
[0187] 116. A polyolefin blend according to any one of clauses 93 to 115, wherein the first polyolefin is provided in a loading of 0.05 wt% to 3 wt% relative to the total mass of the polyolefin blend.
[0188] 117. A polyolefin blend according to any one of clauses 93 to 116, wherein the first polyolefin is provided in a loading of 0.1 wt% to 2.5 wt% relative to the total mass of the polyolefin blend.
[0189] 118. A polyolefin blend according to any one of clauses 93 to 117, wherein the first polyolefin is provided in a loading of 0.5 wt% to 2 wt% relative to the total mass of the polyolefin blend.
[0190] 119. A polyolefin blend according to any one of clauses 93 to 118, wherein the first polyolefin is provided in a loading of 1 wt% to 2 wt% relative to the total mass of the polyolefin blend.
[0191] 120. A polyolefin blend according to any one of clauses 93 to 119, wherein the first polyolefin is provided in a loading of about 2 wt% relative to the total mass of the polyolefin blend.
[0192] 121. A polyolefin blend according to any one of clauses 93 to 120, wherein the second polyolefin is selected from polyethylene (PE), polypropylene (PP), and mixtures thereof.
[0193] 122. A polyolefin blend pursuant to Clause 121, wherein the second polyolefin is PE.
[0194] 123. A polyolefin blend pursuant to Clause 122, wherein PO is PE and the second polyolefin is PE.
[0195] 124. A method for preparing a polyolefin blend of any one of clauses 93 to 123, the method comprising melt blending a first polyolefin with a second polyolefin.
[0196] 125. The method according to Clause 124, wherein melt blending is carried out via co-extrusion.
[0197] 126. The method according to clauses 124 or 125, wherein melt blending is carried out at 100°C to 200°C.
[0198] 127. The method according to any one of clauses 124 to 126, wherein melt blending is carried out at 120°C to 150°C.
[0199] 128. The method according to any one of clauses 124 to 127, wherein melt blending is carried out at 130°C.
[0200] 129. Use of functionalized polyolefins as antimicrobial polymer additives as defined in any of Clauses 1 to 58 or 92.
[0201] 130. A method for imparting antimicrobial properties to a surface, the method comprising applying a functionalized polyolefin as defined in any one of Clauses 1 to 58 or 92, or a polyolefin blend as defined in any one of Clauses 93 to 123, to the surface.
[0202] 131. The method according to Clause 130, wherein the functionalized polyolefin or polyolefin blend is applied in the form of a film.
[0203] 132. A surface or article comprising (i) a functionalized polyolefin as defined in any one of Clauses 1 to 58 or 92, or (ii) a polyolefin blend pursuant to any one of Clauses 93 to 123.
[0204] 133. Articles of manufacture pursuant to Clause 132, wherein the article of manufacture is a medical device.
[0205] 134. Articles of manufacture pursuant to Clause 133, wherein the medical device is a catheter.
[0206] The present invention will now be described with reference to the following embodiments and accompanying drawings, which are for illustrative purposes only and should not be construed as limiting the invention.
[0207] Example
[0208] Example 1. Catalytic chain growth (CCG) reaction
[0209] Long-chain 1-iodoalkanes are prepared via a CCG reaction starting from diethylzinc and ethylene. An example of this is shown in Scheme 1. The bis(imino)pyridine iron complex is activated with MAO to insert the ethylene monomer into the C-Zn bond of ZnEt2, thereby producing ZnPE2 with a narrow molecular weight distribution.
[0210]
[0211] Option 1
[0212] Preparation of Zn(PE)2
[0213] Zn(PE)₂ was prepared as described in WO03014046. (6.5 mg, 0.01 mmol) of (2,6-diacetylpyridinebis(2,6-diisopropylaniline))FeCl₂ was placed in 5 mL of toluene, yielding a blue suspension. Upon addition of 100 equivalents of MAO (0.93 mL of 7 wt% toluene solution), the solution turned orange. Adding ZnEt₂ dissolved in 25 mL of toluene (3 mmol, 2.63 mL of 15 wt.% toluene solution) to the orange solution yielded a yellow solution. Polymerization was initiated by adding ethylene (1 bar (g)) at room temperature. After the desired time (typically less than 1 hour), polymerization was stopped by shutting off the ethylene supply. The resulting precipitate was filtered and washed several times with toluene under N₂ to obtain 1.94 g of Zn(PE)₂ polymer. PE contamination due to partial hydrolysis was frequently observed during post-processing; therefore, in-situ conversion of Zn(PE)₂ without separation is recommended. 1 H-NMR (400 MHz, d8-toluene, 100ºC): δ 1.53 (m, ZnCH2CH2), 1.36 (CH2), 0.83 (CH3), 0.30 (t, J = 8Hz, ZnCH2). 13 C10 NMR (400 MHz, d8-toluene, 100 ºC): 37.1 (ZnCH2CH2), 26.8 (CH2CH3), 16.3 (ZnCH2), 14.2 (CH3). IR (ATR, pure sample): cm⁻¹ -1 2911 (νCHas), 2846 (νCHs), 1467 (δCH2), 1379 (δCH3), 717 (δCH2), 625 (ρZnCH2).
[0214] Preparation of PE-I
[0215] Zn(PE)2 (28 mg, 0.028 mmol, Zn(C) 34 H 69 2) The mixture was suspended in 10 ml of toluene. A 5 ml toluene solution of iodine (14.2 mg, 0.056 mmol, 2 equivalents) was added to the mixture over 1 hour at room temperature. The reaction was maintained at 60 °C for 1 hour. The reaction was quenched by adding the reaction mixture to 20 ml of methanol and 1 ml of 1 M HCl aqueous solution. The precipitate was filtered and dried to give the product polymer (16 mg, 48% yield). The product was then... 1 H analysis indicated 84% iodine functionalization. 1H-NMR (400 MHz, CDCl3, 25 ºC): δ 3.19 ppm (t, 2H, 3 J H-H = 7 Hz, CH2-I), 1.82 ppm (m,2H, CH2-CH2-I), 1.25 ppm (s, 67H, -CH2-), 0.88 ppm (t, 3H, 3 J H-H = 7 Hz, -CH3).
[0216] Example 2. Changes in chain length of Zn(PE)2 under different Zn / Fe ratios
[0217] CCG reactions provide complete control over the chain length of growing alkanes by adjusting the Zn / Fe ratio.
[0218] In the absence of the chain transfer agent ZnEt2, the catalyst system polymerized ethylene with very high activity and produced high molecular weight polyethylene (Run 1 in Table 1). Catalytic chain growth for Zn(PE) formation was observed at Zn / Fe ratios > 300 equivalents. While a larger Zn / Fe ratio would produce more Zn(PE)2, this would result in shorter chains over a given time and would also reduce catalytic activity, likely due to ZnEt2 competing with ethylene for binding to the catalyst.
[0219] Table 1. Changes in chain length of Zn(PE)2 under different Zn / Fe ratios.
[0220]
[0221] Conditions: catalyst (10 µmol), MAO (100 equivalents), toluene solvent (30 mL), room temperature, 1 barg ethylene, 1 hour reaction time. a λ = the average number of inserted ethylene units, determined by GC analysis. b C n =Average chain length, through 13 C-NMR analysis was performed. c No exchange to zinc was observed.
[0222] Example 3. Synthesis of antimicrobial additives
[0223] PE-N-(4-chlorophenyl)-N'-alkyliminodicarbonimide diamide (PE-CH), PE-dimethylbenzylammonium iodide (PE-DMBA), and PE-pyridinium iodide (PE-PYR) were synthesized as shown in Scheme 2.
[0224]
[0225] Option 2
[0226] PE-triphenylphosphonium iodide and polyvinyltributylphosphonium iodide were also synthesized.
[0227] Synthesis of p-chlorophenylcyanoguanidine
[0228] 0.7 g sodium dicyandiamide (7.84 mmol) and 1.0 g 4-chloroaniline (7.84 mmol) were dissolved in 40 mL of water. 0.7 mL of HCl (aq, 37%, 7.8 mmol) was added to this aqueous solution, and the mixture was stirred at 60 °C for 3 hours. The mixture was then cooled to 0 °C to give a white powder. The product was filtered through filter paper and washed with 50 mL of diethyl ether to give 1.36 g of white powder (90% yield). 1 H NMR (500 MHz, DMSO, 393 K) δ 6.64 (s, 2H), 7.33 (d, J = 7.5Hz, 2H), 7.36 (d, J = 7.3 Hz, 2H), 8.83 (s, 1H). 13 C NMR (101 MHz, DMSO) δ117.42, 123.28, 127.92, 129.12, 137.53, 159.89 ppm.
[0229] Synthesis of PE-NH2
[0230] A two-step process can be used to convert PE-I to PE-NH2 via PE-N3 and / or subsequent reduction with LiAlH4 or H2 and Pd / C. The latter method, as used in the examples herein, for the preparation of PE-N-(4-chlorophenyl)-N'-alkyliminodicarboximide diamide, works well for shorter alkyl chains that are readily soluble in hot toluene and separated from the catalyst by filtration; however, this can be problematic for longer alkyl chains. A more convenient one-step method can be used. This avoids the use of azides and LiAlH4 and involves simply reacting PE-I with excess liquid ammonia in toluene at elevated temperature and pressure. Excess ammonia is required to avoid over-alkylation.
[0231] Option 1. Two-step synthesis of PE-NH2
[0232] Approximately 1g of PE-I (C 30 H 61-I (approximately 1.8 mmol, 1 equivalent) and 0.14 g of sodium azide (2.2 mmol, 1.2 equivalent) were added to 20 mL of DMF. The reaction was purged with nitrogen and stirred at 120 °C for 4 hours. Subsequently, the suspension was filtered, washed with methanol, and dried under vacuum overnight to give 0.75 g of PE-N3 as a white powder (90% yield). 30 H 61 The functionality of -N3 was determined by FTIR spectroscopy at 2094 cm⁻¹. -1 The presence of a peak at (N3) confirms this, and through... 1 Quantitative analysis was performed using H NMR spectroscopy. 1 ¹H NMR (500 MHz, d²-TCE / 1,2,4-trichlorobenzene, 363 K) δ 1.03 – 1.07 (t, J = 6.8 Hz, 3H), 1.35– 1.56 (d, J = 4.0 Hz, 72H), 1.70 – 1.75 (m, 2H), 3.33 – 3.38 (t, J = 6.9 Hz, 2H) ppm. 13 C NMR (500 MHz, d2-TCE / 1,2,4-trichlorobenzene, 363K) δ 12.81, 21.59, 27.74 –28.53 (m), 28.69, 29.08, 30.90, 50.68 ppm.
[0233] Add 0.5g of PE-N3 (C 30 H 61 N3 (approximately 1 mmol), 20 mg Pd / C, and 10 mL of toluene were added to a 100 mL Hastelloy Parr reactor. The reactor was sealed, purged with nitrogen, and the hydrogen pressure was set to 10 bar at room temperature. The reaction mixture was stirred at room temperature for 20 hours. The reaction mixture dissolved in toluene was heated to 80 °C and then hot-filtered through a glass fiber filter to remove the Pd / C catalyst. The filtrate was then cooled to room temperature and poured into methanol to give PE-NH2 as a white powder precipitate. The white powder was washed with methanol and dried under vacuum overnight. Yield: 0.42 g (85%). 30 H 61 The purity of -NH2 was confirmed by FTIR, as shown at 2094 cm⁻¹. -1 The azide peak at (N3) disappears and at 3333 cm⁻¹ -1 An amine peak appears at [location] (NH stretching), and [it is observed] via [other pathways]. 1Quantitative analysis by ¹H NMR (500 MHz, d²-TCE / 1,2,4-trichlorobenzene, 363 K): δ 0.84–0.91 (m, 3H), 1.22–1.43 (s, 22H), 2.53–2.61 (t, J = 6.7 Hz, 2H) ppm. 13 CNMR (500 MHz, d2-TCE / 1,2,4-trichlorobenzene, 363K) δ 12.81, 21.58, 25.79, 27.78 – 29.71(m), 30.89, 39.08 ppm.
[0234] Option 2. One-step synthesis of PE-NH2
[0235] Weigh out 700mg PE-I (C 42 H 85 -I, approximately 1 mmol) was transferred to a 100 mL Hastelloy Parr autoclave. Then, 20 mL of toluene and 30 mL (approximately 1200 mmol) of liquid ammonia (cooled to -33°C) were added to the autoclave, while the reaction vessel was kept cooled in a dry ice / acetone bath. The autoclave was sealed and heated to room temperature, then gradually heated to 60°C with stirring. When the system reached 60°C, the pressure in the autoclave reached 20 bar. After 10 hours, the autoclave was cooled to room temperature, and the pressure was gradually released. The mixture was poured into methanol, yielding a white precipitate. The white solid was filtered and washed with 50 mL of methanol. The final product was collected and dried overnight in a vacuum oven at 40°C. The product mass was 494 mg (83% yield), and the purity of PE-NH2 was 92% (a small amount of (PE)2NH was also observed, through...). 1 The H NMR spectrum is approximately 8%.
[0236] Synthesis of N-(4-chlorophenyl)-N'-alkyliminodicarboximide diamide (PE-CH)
[0237] 5.3 mmol C n H 2n+1 -NH2, 5.3 mmol of p-chlorophenylcyanoguanidine, 5.3 mmol of HCl, and 50.0 mL of butanol were added to a round-bottom flask. The mixture was stirred overnight at 150 °C under reflux. The product was separated by removing the butanol under vacuum and washing the powder three times with diethyl ether to obtain a white powder. 1H NMR (500 MHz, DMSO, 393K) δ 0.82 – 0.99(m, 3H), 1.11 – 1.41 (m), 1.57 – 1.71 (m, 2H), 2.76 – 2.85 (m, 2H), 6.87 (s,2H), 7.22 – 7.35 (d, J = 7.5 Hz, 2H), 7.38 – 7.50 (d, J = 7.4 Hz, 2H), 7.98(s, 3H). 13 C NMR (126 MHz, DMSO) δ 12.89, 17.88, 21.19, 28.20, 30.50, 34.04, 39.34, 122.58, 127.52, 136.52, 145.24, 156.38 ppm.
[0238] Synthesis of Alkylpyridinium Iodide (PE-PYR)
[0239] 3.0g C 68 -H 137 -I (2.78 mmol) was refluxed in 20 mL of pyridine at 150 °C for 48 hours to give an orange solution. After cooling to room temperature, the product was filtered through filter paper to give a green solid, which was then washed three times with 30 mL of methanol and placed in a vacuum oven at 40 °C overnight. The product was then ground to give 2.4 g of light green powder (78% yield). 1 ¹H NMR (500MHz, d²-TCE / 1,2,4-trichlorobenzene½ v / v, 393K) δ 1.07 (t, J = 6.6 Hz, 3H), 1.47 (m, 86H), 2.27 (m, 4H), 5.10 (t, J = 4.8Hz, 2H), 8.38 (m, 2H), 8.84 (m, 1H), 9.50 (d, J = 7.5 Hz, 2H). 13 C NMR (101 MHz, d2-TCE / 1,2,4-trichlorobenzene½ v / v, 393 K) δ12.70, 21.67, 23.55, 25.80, 28.12, 29.19, 31.02, 53.84, 59.94, 131.12, 145.43, 148.32.
[0240] Synthesis of PE-dimethylbenzylammonium iodide (PE-DMBA)
[0241] 3.0g C 68 -H 137I (2.78 mmol) was refluxed in 20 mL of N,N-dimethylbenzylamine at 150 °C for 48 hours to give a black solution. The reaction mixture was then cooled to room temperature, and the product was filtered through filter paper. The product was washed three times with 30 mL of methanol and dried overnight in a vacuum oven to give 2.6 g of brown powder (76% yield). 1 ¹H NMR (500 MHz, d²-TCE / 1,2,4-trichlorobenzene½ v / v, 393 K) δ 1.06 (t, J = 7.0 Hz, 3H), 1.47 (m, 75H), 1.86–2.12 (m, 2H), 2.84 (s, 6H), 2.99–3.15 (m, 2H), 7.49 (m, 5H). 13 C NMR (101MHz, d2-TCE / 1,2,4-trichlorobenzene½ v / v, 393K) δ 12.80, 21.57, 23.05, 25.90, 28.02, 29.09, 30.88, 41.44, 49.10, 56.97, 73.27, 115.54, 122.90, 144.32.
[0242] Synthesis of PE-triphenylphosphonium iodide
[0243] Under a nitrogen atmosphere, PE-I(C 60 H 121 I (0.91 g, about 1.0 mmol) and excess PPh3 (1.31 g, 5.0 mmol) were dissolved in toluene (10 mL). The reaction mixture was heated under reflux at 120 °C for 48 h and then quenched with methanol (100 mL) to give a white solid, which was collected by filtration, washed with methanol and dried under vacuum (0.84 g, 0.72 mmol, 72% yield).
[0244] 1 ¹H NMR (70 °C, 400 MHz, C6D6 / tetrachloroethylene (1 / 2 volume / volume)): δ = 0.84 (3H,t, CH3, J = 8 Hz), 1.25 (m, CH2), 4.2 (m, 2H, PCH2), 6.96–7.95 (15H, m) ppm. 31 P{ 1 H NMR (70 °C, 162 MHz, C6D6 / tetrachloroethylene (1 / 2 volume / volume)): δ = 25.29 ppm.
[0245] Synthesis of PE-tributylphosphonium iodide
[0246] Under a nitrogen atmosphere, PE-I(C 60 H 121 I (0.91 g, about 1.0 mmol) and PBu3 (1.25 mL, 5.0 mmol) were dissolved in toluene (10 mL). The reaction mixture was heated under reflux at 120 °C for 48 hours and then quenched with methanol (100 mL) to give a white solid, which was collected by filtration, washed with methanol and dried under vacuum (0.62 g, 0.56 mmol, 56% yield).
[0247] 1 ¹H NMR (120 °C, 400 MHz, d²-tetrachloroethane / 1,2,4-trichlorobenzene (1 / 2, volume / volume)): δ = 1.05 (3H, t, CH₃, J = 4 Hz), 1.16 (9H, t, J = 4 Hz), 1.47 (m), 2.66 (8H, m) ppm. 31 P{ 1 ¹H NMR (120 °C, 162 MHz, d2-tetrachloroethane / 1,2,4-trichlorobenzene (1 / 2, volume / volume)): δ = 33.44 ppm.
[0248] Example 4. Conversion of PE-NH2 to PE-CH
[0249] From C 12 To C 68 Amino-terminal functionalized PE (PE-NH2) of different molecular weights has been used to prepare PE-CH additives. Due to the low solubility of long alkyl chains in butanol, the total functionalization of PE-CH decreases with increasing alkyl chain molecular weight (Table 2). The conversion rate of PE-NH2 to PE-CH ranges from C2... 12 H 25 -90% of NH2 goes to C 68 H 137 -NH2 accounts for 85%, leading to C 12 H 25 -CH and C 18 H 37 -CH has a functionality of 90%, C 30 H 61 -CH has a functionality of 85% and C 68 H 137 -CH has a functionality of 75%.
[0250] Table 2. Synthesis of N-(4-chlorophenyl)-N'-alkyliminodicarbonimide diamide (PE-CH).
[0251]
[0252] C n =Average chain length, through 13 C NMR spectroscopy analysis was used to determine the functionality and yield. 1 Determined by ¹H NMR spectroscopy. Conversion rate = PE-CH functionality (%) / PE-NH₂ functionality (%).
[0253] Example 5. Converting PE-I to PE-PYR
[0254] Using nucleophilic substitution (S N 2) Preparation of alkylpyridinium iodides (PE-PYR) of different molecular weights by reaction. Toluene was used as a solvent to react C 18 H 37 -I reacts with pyridine to achieve an 86% conversion, while changing the solvent to butanone yields a 90% conversion. The slight increase in conversion when using butanone as the solvent may be due to the change in solvent polarity. N 2. The reaction is sensitive to the solvent, and polar aprotic solvents generally show higher conversion rates.
[0255] When using a longer alkyl chain, such as C 68 H 137 -I, the reaction was unsuccessful when using butanone, 1,2,4-trichlorobenzene, or N,N-dimethylformamide. These solvents are used because they can dissolve long alkyl chains at higher temperatures. Due to S N 2. The reaction rate depends on the concentrations of PE-I and pyridine; higher reagent concentrations result in better conversion rates. Therefore, C 68 H 137 -I was refluxed in pyridine at 150 °C to obtain 90% conversion and 81% PE-PYR functionalization. Due to the low solubility of the PE chain in pyridine, increasing the alkyl chain length of PE-I to 180 carbons resulted in 36% conversion and only 30% PE-PYR functionality.
[0256] Table 3. Synthesis of alkylpyridinium iodide (PE-PYR).
[0257]
[0258] a) Percentage of sensibility passed 1 b) Conversion rate = PE-PYR functionality (%) / PE-I functionality (%). The average chain length of PE-I was determined by H NMR spectroscopy. 13 C NMR determination.
[0259] Example 6. PE-I to PE-DMBA
[0260] The synthesis of n-alkyl dimethyl benzyl ammonium iodide is carried out by reacting PE-I of different molecular weights with N,N-dimethyl benzylamine.
[0261] Butanone due to the completion of S N The ability of the reaction to proceed has been reported multiple times. However, long-chain functionalized alkanes have very low solubility in butanone. Therefore, when butanone is used as a solvent, C... 68 H 137 The reaction of -I with N,N-dimethylbenzylamine was unsuccessful. Similar results were observed when 1,2,4-trichlorobenzene or N,N-dimethylformamide were used as the solvent. Due to S N 2. The reaction rate depends on the concentration of the reactants. (The last part, "C," appears to be a typo 68 H 137 -I was refluxed in pure N,N-dimethylbenzylamine at 150 °C to give 82% conversion and 80% functionality. In contrast, C 180 H 361 -I was refluxed in N,N-dimethylbenzylamine at 150 °C, yielding only 36% conversion and 30% PE-DMBA functionality.
[0262] Table 4. Synthesis of PE-dimethylbenzylammonium iodide (PE-DMBA).
[0263]
[0264] a) Functionality yield through 1 b) Conversion rate = PE-DMBA functionality (%) / PE-I functionality (%). The average chain length of PE-I was determined by H NMR spectroscopy. 13 C NMR spectroscopy analysis.
[0265] Example 7. Extrusion and Thermal Analysis
[0266] Melt blending of LDPE with antimicrobial PE additives
[0267] The melt blending of LDPE with antimicrobial PE additives was carried out using a co-rotating twin-screw extruder (Eurolab XL, Thermo Fisher Scientific, Karlsruhe, Germany). This twin-screw extruder was equipped with a screw with a diameter of 16 mm and an L / D ratio of 25. During the manufacture of the LDPE / additive blend, the extruder's feed zone, four subsequent zones, and die temperature were all set to 130°C. The extrudate was processed at 15 rpm in the first cycle, 30 rpm in the second cycle, and 50 rpm in the third cycle. After each cycle, the extrudate was pelletized into 2 mm pellets using a pelletizer (Haake VariCut, Thermo Fisher Scientific, Karlsruhe, Germany), mixed in a container, and fed back into the extruder for the next cycle.
[0268] LDPE / PE-CH extrusion
[0269] Mix 10g LDPE with 0.4g C 66 H 133 The LDPE / PE-CH blend was extruded using a co-rotating twin-screw extruder (Eurolab XL, Thermo Fisher Scientific, Karlsruhe, Germany). The two materials were first mixed in a container and then fed into the extruder. During the manufacture of the LDPE / PE-CH blend, the extruder's feed zone, four subsequent zones, and die temperature were all set to 130°C. The extrudate was processed at 15 rpm in the first cycle, 30 rpm in the second cycle, and 50 rpm in the third cycle. After each cycle, the molten extrudate was recrystallized in air, then cut into 2 mm pellets using a pelletizer (Haake VariCut, Thermo Fisher Scientific, Karlsruhe, Germany), mixed in a container, and fed into the extruder for the next cycle.
[0270] Table 5 shows the melt blending of antimicrobial additives with LDPE using different additive loadings (wt%).
[0271] Table 5. Melt blending of antimicrobial additives with LDPE.
[0272]
[0273] Differential scanning calorimetry (DSC)
[0274] DSC measurements were performed using a Discovery DSC (TA Instruments, Hertfordshire, UK) under a nitrogen atmosphere to evaluate the thermal behavior of LDPE and additives. Samples ranging from 2 mg to 5 mg were used for each measurement. Samples were heated from 0 °C to 200 °C at a rate of 10 °C / min, then cooled at a rate of 10 °C / min. Samples were then reheated to 200 °C at a rate of 10 °C / min. Data were processed using Trios software.
[0275] The percentage of crystallinity in the LDPE and antimicrobial LDPE blends was measured using a second heating cycle of DSC analysis. Crystallinity was determined by quantifying the heat of melt (ΔH) associated with the melting stage. m And it is determined according to the following equation, which is normalized to the heat of fusion (ΔH0) of 100% crystalline polyethylene:
[0276]
[0277] Where ΔH m ΔH0 is the heat of fusion (J / g), ΔH0 is the heat of fusion of 100% crystalline PE (293J / g), and w is the fraction of LDPE in the blend.
[0278] Table 6 shows the experimental data obtained from the DSC analysis of the samples. Because controlled crystallization occurred during the first cooling cycle, the second heating cycle in the DSC scan was considered. This allows for a more accurate comparison of the crystallinity of the samples. Pure LDPE showed a crystallinity of 32.3%, and, generally, the addition of additives was observed to lead to a decrease in crystallinity. LDPE with C 66 H 133 -CH and C 18 H 37 Blends of -CH exhibit similar behavior, resulting in higher crystallinity at 2 wt% loading compared to 4 wt% loading (Table 6). As the alkyl chain length decreases from C... 18 Increase to C 66 The crystallinity of the blends increased slightly. Adding 2 wt% loadings of PE-PYR and PE-DMBA to LDPE showed very little change in the percentage of crystallinity, while 4 wt% loadings of PE-DMBA reduced the crystallinity from 32.3% to 21.8%. Generally, the addition of antimicrobial additives to LDPE has the least effect on the melt temperature and crystallinity of LDPE, indicating minimal change in the mechanical properties of the polymer.
[0279] Table 6. DSC measurements of LDPE and LDPE / antimicrobial PE additive blends via melt blending using a second heating cycle.
[0280]
[0281] TGA
[0282] Thermochemical thermogravimetric analysis (TGA) was also performed to assess the effect of additive addition on the degradation temperature of LDPE. Thermal degradation measurements were performed using a Mettler Toledo TGA. Samples ranging from 5 mg to 10 mg were used for each measurement. The temperature was increased from room temperature to 800 °C at a rate of 10 °C / min under a nitrogen atmosphere.
[0283] In all cases, further TGA measurements were performed, with the degradation temperature increasing by 20°C from 435°C to 50°C. The results showed that the thermal degradation of the blend was not negatively affected.
[0284] Example 8. Extraction Experiment
[0285] To investigate the entanglement of antimicrobial additives in LDPE, several extraction attempts were conducted using two different methods.
[0286] Additives are extracted using stirring.
[0287] 1g of LDPE / C with a loading of 4wt.% 18 H 37 The CH blend was pressed into a 1.5 mm thick film. The film was then placed in a vial equipped with a magnetic stirrer. Extraction was performed using hexane at room temperature for 24 hours. The collected extract was then placed under vacuum to remove volatiles. No precipitate was collected using this extraction method.
[0288] Additives were extracted using a Soxhlet extractor.
[0289] 1g of LDPE / C with a loading of 4wt.% 18 H 37 -CH blends were pressed into films with a thickness of 1.5 mm. The films were then placed in an extraction chamber for Soxhlet extraction. Extraction was performed using hexane at 80°C for 5 hours. The samples were then washed with hot toluene at 80°C to dissolve any leached additives. Control experiments demonstrated that hot toluene at 80°C dissolved antimicrobial additives, and the extract could pass through a Soxhlet extraction chamber. The collected extract was then placed under vacuum to remove volatiles. In this case, when using LDPE / C with a loading of 4 wt.%... 18 H 37 When the -CH blend was prepared, 9 mg of additive was collected, accounting for 22.5% of the total additives in the sample. The collected additives were then characterized by FTIR spectroscopy to confirm the C... 18 H 37 -CH vibration band, including 1634cm -1 C=N stretching at 1250cm-1 CN stretching and 3100cm -1 Up to 3500cm -1 The NH bond vibrates at that location.
[0290] The extraction performed using the first method did not show any additive leaching because no extract was collected. In the second method using a Soxhlet extractor, when LDPE-C... 18 H 37 -CH-4% was observed to leach additives after hexane extraction at 80°C for 5 hours. To ensure the leached additives passed through the extraction chamber, the sample was washed with hot toluene at 80°C. (Note: The last sentence appears to be incomplete and possibly refers to a different topic.) 18 Additive leaching was only observed when synthesizing the active antimicrobial agent. The amount of leached additive accounted for 23% of the total additive loading (Table 7). When using LDPE-C n H 2n+1 No residue was collected when the -CH blend was used and n=30 and 66. (The last part, "C", appears to be a typo and can be left as is.) 66 H 133 Increasing the CH loading to 10% did not show any leaching of the additive. FTIR spectroscopy of the post-extraction blend confirmed the presence of the additive, with a vibrational band of 1634 cm⁻¹. -1 C=N stretching and 1250cm -1 CN expansion at the location. Also for LDPE-C with a 4wt% load. 66 H 133 -PYR was used for Soxhlet extraction. Under the same conditions, no leaching of the additive from the LDPE matrix was observed. FT-IR spectroscopy confirmed the presence of the additive, with a vibrational band at 1634 cm⁻¹. -1 C=N stretching at the point, 1373cm -1 Aromatic CN stretching and 1165cm -1 CN scaling at the location.
[0291] Table 7. Attempts to use Soxhlet extraction.
[0292]
[0293] Example 9. Antimicrobial activity
[0294] LDPE-C was tested 66 H 133 -DMBA, LDPE-C 66 H 133 -PYR and LDPE-C 66 H 133-CH antimicrobial activity. For each antimicrobial additive, a total of six samples were prepared at two different loadings (2 wt% and 4 wt%). The first step involved culturing *E. coli* on agar plates. The microbial suspension was then diluted with 1.0 g tryptone (pancreatic digest of casein), 8.5 g NaCl, and 1000 ml water. To preserve viable bacteria during the counting process, a solution of 15.0 g tryptone, 5.0 g soy peptone, 5.0 g NaCl, 15.0 g agar, and 1000 ml water was used. The surfaces of the samples and reference samples were first sterilized with ethanol, and samples with dimensions of 1 cm × 1 cm and a thickness of 1 mm were used. A 10 µL bacterial suspension containing a known number of viable bacteria was exposed to the samples for 5 minutes. Subsequently, the viable bacteria were washed with a recovery solution containing 1.0 g tryptone, 5.0 g NaCl, 5.0 g polysorbate, and 1000 ml water. The final step involved counting the remaining viable bacteria to determine the killing activity.
[0295] All six samples showed efficacy in killing *E. coli*, differing only in the degree of viable bacteria remaining on the surface. Table 8 lists the percentage of bacteria remaining after 5 minutes of contact with the LDPE / additive samples. LDPE-C 66 H 133 -DMBA showed the lowest killing efficiency among all six samples, at 88% at both 4wt% and 2wt% loadings. LDPE-C 66 H 133 -PYR exhibited a peak killing efficiency of 97% at both 4wt% and 2wt% loadings. LDPE-C 66 H 133 -CH also showed excellent efficiency of 96% at 4wt% and 2wt% loadings (Table 8 and 10). Figure 1 Statistical significance was calculated for the obtained antimicrobial activity data, with p-values less than 0.001. The close match of antimicrobial activity at 2 wt% and 4 wt% loadings indicates that the surface is saturated at 2 wt% and that higher loading percentages are unlikely to have a substantial effect.
[0296] Table 8. Antimicrobial efficiency of various LDPE / PE-X blends against Escherichia coli MC1000.
[0297]
[0298] Conditions: Bacterial strain: *Escherichia coli* M1000; exposure time: 5 minutes. Statistical analysis was performed using a two-tailed Student's t-test. Data are expressed as the mean ± standard deviation of two biological replicates.
[0299] Since PE additives contain an average of 66 carbon alkyl chains, the weight percentage of the actual active antimicrobial component can be calculated. Figure 2 The molecular weight fraction of the active antimicrobial compound relative to the alkyl chain is shown for each additive. The actual loading percentage of the active material was calculated by considering the weight percentage of the additive in LDPE, the functionality percentage of the additive, and the weight fraction of the active ingredient in the additive (Table 9). Table 9 shows that incorporating less than 1 wt% of the active antimicrobial agent into LDPE is sufficient to create an antimicrobial LDPE surface. For example, a loading of 0.3 wt% of pyridinium iodide is sufficient to demonstrate a 97% bactericidal efficiency. Low loading percentages are crucial in antimicrobial packaging applications.
[0300] Table 9. Actual loading (wt%) of active antimicrobial compounds.
[0301]
[0302] a) The weight fraction of active antimicrobial compounds in PE additives was obtained from... Figure 2 b) Percentage of functionality of additives used 1 Obtained by H NMR.
[0303] c)
[0304] Example 10. Activity of phosphonium-based additives
[0305] The phosphonium-based additive was synthesized as described in Example 3. The additive was then blended with LDPE and tested as described below.
[0306] Methods for blending functionalized PE additives and LDPE
[0307] Weigh the PE-PR3I polymer and LDPE according to the desired weight fraction and transfer them to a 100 ml flask. Add 50 ml of dry toluene while stirring, and gradually heat the flask at 120 °C for 10 minutes. When all the products have dissolved and mixed completely, cool the flask. At this point, the product appears as a gel. Precipitate the product in methanol, filter and wash with methanol, and dry overnight in a vacuum oven at 60 °C to obtain a white powder. Then, LDPE / PE-P n Bu3I polymer blends were hot-pressed into discs with a diameter of 4 cm.
[0308] PE-P n Bu3I antimicrobial test
[0309] Antimicrobial performance was tested using *E. coli* cultured on agar plates and applied to various 1×1 cm LDPE / PE-P plates.n Bu3I polymer blocks. In LDPE, PE-P was added at 2 wt%, 4 wt%, and 10 wt%. n Bu3I was used with three different additive loadings, and the survival rate of *E. coli* was determined after different exposure times of 3 minutes (Table 10) and 1 hour (Table 11). The test results were compared with pure LDPE control samples prepared and heat-pressed under the same conditions. Survival rate is expressed as a percentage relative to the control samples of pure LDPE, with the survival rate of the control samples normalized to 100%.
[0310] Table 10. Survival rate after 3 minutes of exposure.
[0311]
[0312] Table 11. Survival rate 1 hour after exposure.
[0313]
[0314] It should be understood that the above description is by way of example and not a limitation on the scope of the appended claims (including any equivalents included within their scope). Various modifications are possible and will be apparent to those skilled in the art. Similarly, features of the described embodiments may be combined with any suitable aspect above, and optional features of any aspect may be combined with any other suitable aspect.
Claims
1. A functionalized polyolefin of formula PO-X, wherein: PO is a polyolefin with a chain length of at least 20 carbon atoms; and X is a positively charged functional group or a functional group that can form a cation at pH 7.
2. The functionalized polyolefin according to claim 1, wherein PO is polyethylene (PE) or polypropylene (PP).
3. The functionalized polyolefin according to claim 2, wherein PO is polyethylene (PE).
4. The functionalized polyolefin according to any one of the preceding claims, wherein X or the cation is selected from ammonium cations, phosphonium cations, pyridinium cations, imidazolium cations, amidonium cations and guanidinium cations.
5. The functionalized polyolefin according to claim 4, wherein X or the cation is selected from ammonium cations, pyridinium cations, and guanidine cations.
6. The functionalized polyolefin according to any one of the preceding claims, wherein X is selected from: , and .
7. The functionalized polyolefin according to any one of the preceding claims, wherein the PO has a chain length of 20 to 100 carbon atoms.
8. The functionalized polyolefin according to claim 7, wherein PO has a chain length of 50 to 80 carbon atoms.
9. A method for preparing the functionalized polyolefin according to any one of claims 1 to 8, the method comprising: Zn(PO)₂ reacts with iodine to obtain PO₄⁻I; as well as To obtain PO-X by reacting PO-I, PO has a chain length of at least 20 carbon atoms.
10. The method according to claim 9, wherein Zn(PO)2 is produced by polymerizing olefins in the presence of alkyl zinc and a catalyst system.
11. The method according to claim 9 or 10, wherein reacting PO-I to obtain PO-X comprises reacting PO-I with a tertiary amine.
12. The method according to claim 9 or 10, wherein reacting PO-I to obtain PO-X comprises reacting PO-I with pyridine.
13. The method of claim 9 or 10, wherein reacting PO-I to obtain PO-X comprises: PO-I is reacted with azides to obtain PO-N3; The azide was reduced to obtain PO-NH2; and To react PO-NH2 with cyanoguanidine.
14. The method of claim 9 or 10, wherein reacting PO-I to obtain PO-X comprises: Reacting PO-I with NH3 to obtain PO-NH2; and To react PO-NH2 with cyanoguanidine.
15. The method of claim 9 or 10, wherein reacting PO-I to obtain PO-X comprises reacting PO-I with tertiary phosphine.
16. A functionalized polyolefin that can be obtained by the method of any one of claims 9 to 15.
17. A polyolefin blend comprising a first polyolefin and a second polyolefin, wherein the first polyolefin is a functionalized polyolefin as defined in any one of claims 1 to 8 or 16.
18. The polyolefin blend of claim 17, wherein the first polyolefin is provided at a loading of 0.01 wt% to 4 wt% relative to the total mass of the polyolefin blend.
19. The polyolefin blend of claim 18, wherein the first polyolefin is provided at a loading of 0.5 wt% to 2 wt% relative to the total mass of the polyolefin blend.
20. The polyolefin blend according to any one of claims 17 to 19, wherein the second polyolefin is selected from polyethylene (PE), polypropylene (PP), and mixtures thereof.
21. The polyolefin blend according to any one of claims 17 to 20, wherein PO is PE and the second polyolefin is PE.
22. A method for preparing a polyolefin blend according to any one of claims 17 to 21, the method comprising melt blending the first polyolefin with the second polyolefin.
23. Use of the functionalized polyolefin as defined in any one of claims 1 to 8 or 16 as an antimicrobial polymer additive.
24. A method for imparting antimicrobial properties to a surface, the method comprising applying a functionalized polyolefin as defined in any one of claims 1 to 8 or 16, or a polyolefin blend as described in any one of claims 17 to 21, to the surface.
25. A surface or article comprising (i) a functionalized polyolefin as defined in any one of claims 1 to 8 or 16, or (ii) a polyolefin blend according to any one of claims 17 to 21.
Citation Information
Patent Citations
Plastic with a biocidal surface and method of making same
EP2824139A1
Plastic having a biocidal surface and method for producing said plastic
US20160150778A1
Chain growth reaction process
WO2003014046A1